2000
DOI: 10.1016/s0032-3861(99)00783-1
|View full text |Cite
|
Sign up to set email alerts
|

Reactive compatibilization of PC/PVDF polymer blends by zinc carboxylate containing poly(methylmethacrylate) ionomers

Abstract: Polycarbonate (PC) has been reacted with a random copolymer of methylmethacrylate and 6 mol% of acrylic acid (poly(MMA-co-AA)) and with this copolymer neutralized (totally or not) by Zn cations. When conducted in solution at 240°C, the reaction leads to the grafting of PC onto the copolymer neutralized or not. In the melt at 235°C, the grafting reaction occurs only when the copolymer is at least partly neutralized. Whatever the experimental conditions (solution or bulk), PMMA does not react with PC, which conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In another study, imide units were copolymerized with MMA in order to improve the compatibility between PC and acrylics through specific interactions or internal repulsion [ 20 ]. Moussaif et al obtained a PMMA-g-PC copolymer that could act as a compatibilizer for the PC/PVDF blend [ 21 ]. Kunar et al melt blended bisphenol-A polycarbonate and poly(butylene terephthalate) with ethylene-n-butylacrylate-glycidylmethacrylate terpolymer at various proportions in order to study the effects of compatibilizers on mechanical, thermal, and flow properties of the blends [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, imide units were copolymerized with MMA in order to improve the compatibility between PC and acrylics through specific interactions or internal repulsion [ 20 ]. Moussaif et al obtained a PMMA-g-PC copolymer that could act as a compatibilizer for the PC/PVDF blend [ 21 ]. Kunar et al melt blended bisphenol-A polycarbonate and poly(butylene terephthalate) with ethylene-n-butylacrylate-glycidylmethacrylate terpolymer at various proportions in order to study the effects of compatibilizers on mechanical, thermal, and flow properties of the blends [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A membrane with a 50% weight ratio of PMMA and PVDF exhibited a lower contact angle than the neat PVDF membrane. A PVDF–polycarbonate blend membrane having a PMMA compatibilizer was reported to have enhanced miscibility and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to utilize the tendency of PVDF to interact with polar polymers, several blend compatibility studies have been reported for blends of PVDF with a variety of ion-containing polymers [14]. Moussaif et al investigated the miscibility of PVDF with poly(methyl methacrylate-co-zinc acrylate) ionomers [15] and polycarbonate grafted with poly(methyl methacrylate-co-zinc acrylate) [16]. These studies showed an increasing tendency toward miscibility with an increase in the ionic functionality of the ionomer.…”
Section: Introductionmentioning
confidence: 99%